Penyelesaian Sengketa Perbankan Syariah di Indonesia - Nurul Ichsan (Universitas Islam Negeri Jakarta, 2015)
This article discussed the settlement of disputes that occur within the Islamic economic institutions (LES). Before being taken to the court, the case of the dispute between the customer and Islamic banking can be solved by consensus or reconciliation (ishlah). Other choice is arbitration Indonesia through sharia arbitration institution called as BASYARNAS (National Arbitration Board). This is what made the different between conventional banking and Islamic economic institution in Indonesia. In Indonesia, there is now also a new provision regarding the institution of the Religious Courts. Although it not optimal implementation, It serves adjudicate disputes that occur between the customer and Islamic banks.DOI: 10.15408/ajis.v15i2.2867